Biogeography and divergence times of genus Macroptilium (Leguminosae) - Espert, Shirley Mary (2010)
Background and aims: Macroptilium is an herbaceous legume genus with eighteen currently accepted species, seven of them with economic importance due to their use as forage, green fertilizer and in medicine. The genus is strictly American, with an unknown biogeographic history. The aim of this study is to infer a biogeographic pattern of Macroptilium and to estimate its divergence times using sequences from the nuclear ribosomal DNA internal transcribed spacers (ITS). Methodology: To study the historical biogeography of Macroptilium, two approaches were used: area optimization on a previously obtained phylogeny, and a dispersal-vicariance analysis. Divergence times were calculated by bayesian methods. Principal results: The analyses revealed that Macroptilium has its origin in the middle Pliocene, with an estimate age that ranges from 2.9 to 4 million years. The biogeographic analyses placed its origin in South America, specifically on the Chaquean sub region, where most of the cladogenetic events of the genus took place. Conclusions: Macroptilium constitutes a further example of the geographic pattern displayed by numerous Neotropical taxa that moved north from South America to dominate the Central America lowlands after the land connection across the Isthmus of Panama was established.